Sarcopenia and frailty as predictors of surgical morbidity and oncologic outcomes in retroperitoneal sarcoma. Issue 5 (9th January 2023) - Nasirishargh, Aida; Grova, Monica; Bateni, Cyrus P.; Judge, Sean J.; Nuno, Miriam A.; Basmaci, Ugur Nur; Canter, Robert J.; Bateni, Sarah B.
Abstract: Background: Retroperitoneal sarcomas (RPS) are rare tumors for which surgical resection is the principal treatment. There is no established model to predict perioperative risks for RPS. We evaluated the association between preoperative sarcopenia, frailty, and hypoalbuminemia with surgical and oncological outcomes. Methods: We performed a prospective cohort analysis of 65 RPS patients who underwent surgical resection. Sarcopenia was defined as Total Psoas Area Index ≤ 1st quintile by sex. Frailty was estimated using the modified frailty index (mFI). Logistic regression models were used to assess predictors of 30‐day postoperative morbidity. The Kaplan–Meier method with log‐rank test was utilized to assess factors associated with overall (OS) and recurrence‐free survival (RFS). Result: Sarcopenia was associated with worse OS with a median of 54 compared with 158 months ( p  = 0.04), but no differences in RFS ( p  > 0.05). Hypoalbuminemia was associated with worse OS with a median of 72 compared with 158 months ( p  < 0.01). MFI scores were not associated with OS or RFS ( p  > 0.05). Sarcopenia, mFI, and hypoalbuminemia were not associated with postoperative morbidity ( p  > 0.05). Conclusion: This study suggests that sarcopenia may be utilized as a measure of overall fitness, rather than a cancer‐specific risk, and the mFI is a poor predictive measure of outcomes in RPS.